Argentina's pathway through financial crisis - Brad Setser; Anna Gelpern (University of Oxford, Global Economic Governance Programme (GEG), 2004)
Political support for Argentina's currency board rested on distributing the early gains from ending hyper-inflation and the spending made possible with access to external credit. When these gains were exhausted and external shocks left the peso overvalued, neither Argentina's political system nor its economy could adjust. The needed adjustment went well beyond simple fiscal tightening: it required deciding who would incur the financial losses associated with the deep contraction needed to correct a real over-valuation in a heavily indebted economy. By 2000, Argentina faced the prospect of further economic contraction, a banking crisis and an external sovereign debt crisis. Even if none of the three crises was avoidable, preemptive action might have made one or more of them less severe. Yet preemption was a political orphan - no political constituency in Argentina argued to bring some pain forward for a chance of less pain down the road, and the IMF and G-7 preferred continued financing to the political risk of supporting a new macroeconomic strategy.
Keywords: 330